Public Ownership of the External World and Private Ownership of Self - Moulin, Hervé; Roemer, John (Journal of Political Economy, 1989)
Liberal political philosophy, represented classically by John Locke and today by libertarians, defends great inequality of economic outcome on the basis that people own themselves and are entitled to establish private property in the external world by virtue of that self-ownership. Contemporary nonlibertarian political philosophers, such as John Rawls and Ronald Dworkin, achieve their relatively egalitarian conclusion by effectively denying self-ownership as a premise. An alternative challenge to liberalism, which does not take the radical starting point of denying self-ownership, is to declare that while certain rights to benefit by virtue of superior skill should be protected (a degree of self-ownership), productive assets in the external world be viewed as publicly owned and not privately appropriable. What allocation mechanisms on a space of possible economies satisfy axioms that are necessary to guarantee both private ownership of self and public or joint ownership of the external world? We propose an axiomatic method for modeling problems in political philosophy of this sort and answer the question posed for a simple model. The result shows that the degree of inequality defended by neo-Lockeanism can be challenged without denying, a priori, self-ownership, its relatively attractive postulate.